Computer Simulation of Cathode Materials for Lithium Ion and Lithium Batteries: A Review - Ma, Ying (Energy & environmental materials (Hoboken, N.J.), 2018)
Driven by the increasing demand for electrochemical energy storage, lithium ion and lithium batteries have been the subject of tremendous scientific endeavors for decades. However, limited energy density, which is bottlenecked by available high‐density cathode materials, has become a critical issue to be solved. Recently, computational studies have played an increasingly important role in the search for the next‐generation high‐density cathode materials. Not only important insights on the battery chemistry have been revealed, but also novel material systems have been proposed. This review highlights recent progresses in the computational studies of cathode materials for lithium ion and lithium batteries. It starts from a brief introduction of the scientific background of lithium ion and lithium batteries, followed by a brief discussion of the working principles of batteries. Different computer simulation techniques are shown to originate from the same quantum mechanical treatment of many‐body systems with different levels of simplifications. Progresses in computational studies of different cathode materials, including intercalation electrode, conversion compounds, sulfur, and organosulfides, are then presented in detail. Finally, the capabilities of computational techniques in the study of cathode materials are summarized, and major challenges are discussed. Computational methods are becoming increasing important in our search for high‐energy‐density electrode materials. This review showcases the versatility of atomistic simulations with a focus on cathode materials for lithium ion and lithium batteries. Progresses and challenges in the study of intercalation and conversion compounds, as well as sulfur and organosulfides, are discussed.